2021
DOI: 10.1177/09612033211016074
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse pregnancy outcomes in Japanese systemic lupus erythematosus patients with prior severe organ manifestations: A single-center retrospective analysis

Abstract: Background Systemic lupus erythematosus (SLE) increases the incidence of adverse pregnancy outcomes (APOs). Nevertheless, most of the data on SLE pregnancies were derived from database studies in which details of the pregnancies were unavailable, and no consensus exists on the risk of APO in patients with prior severe organ manifestations. Methods SLE patients followed by rheumatologists and gynecologists throughout pregnancy at our institute were retrospectively identified, and their data between April 2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…[1][2][3][4][5] Previous studies have shown that a high disease activity, antiphospholipid antibodies, lupus nephritis, and the glucocorticoid dose are risk factors for these APOs. [6][7][8][9][10][11][12][13][14][15][16] We have also shown that disease activity parameters and glucocorticoids were associated with APOs and the Apgar scores of newborns. 11,16 Thus, uncontrolled disease activity and its parameters, such as complement or anti-doublestranded DNA (anti-dsDNA) antibodies, are strongly related to APOs, and the strict control of SLE disease activity in women with SLE who hope to become pregnant is required.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…[1][2][3][4][5] Previous studies have shown that a high disease activity, antiphospholipid antibodies, lupus nephritis, and the glucocorticoid dose are risk factors for these APOs. [6][7][8][9][10][11][12][13][14][15][16] We have also shown that disease activity parameters and glucocorticoids were associated with APOs and the Apgar scores of newborns. 11,16 Thus, uncontrolled disease activity and its parameters, such as complement or anti-doublestranded DNA (anti-dsDNA) antibodies, are strongly related to APOs, and the strict control of SLE disease activity in women with SLE who hope to become pregnant is required.…”
Section: Introductionmentioning
confidence: 73%
“…[1][2][3][4][5] Additionally, these APOs are associated with a high disease activity, lupus nephritis, antiphospholipid antibodies, and glucocorticoid dose during pregnancy. [6][7][8][9][10][11][12][13][14][15][16] Clowse et al found that APOs were increased in patients with high SLE disease activity during pregnancy, particularly for PB (61% with high disease activity compared with low disease activity, p < 0.001). 6 In recent years, several reports have shown an association between APOs and various parameters of disease activities, such as serological biomarkers.…”
Section: Discussionmentioning
confidence: 98%
“…According to a recent review of APOs in SLE pregnancies, 18 the percentages for maternal and fetal complications during pregnancy that were reported in previous studies were as follows: HDP, 0.99%–45%; GDM, 0%–11%; preeclampsia, 5.8%–17%; preterm birth, 9%–56%; miscarriage, 0.4%–18%, SGA, 10%–28.5%; and Apgar score < 7 at 5 min, 0%. Pregnancy outcomes in our institution were therefore within reasonable ranges when compared to those in previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, reduction of glucocorticoid dosage is recommended according to the 2016 EULAR guidelines for use of antirheumatic drugs before and during pregnancy and lactation38 and the 2020 ACR guideline for management of reproductive health in rheumatic and musculoskeletal diseases 39. As we have previously proven that patients with SLE can have favourable pregnancy outcomes even with prior severe organ involvement,40 glucocorticoid discontinuation may further improve pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%